2022
DOI: 10.1038/s41522-022-00351-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumour microbiomes and Fusobacterium genomics in Vietnamese colorectal cancer patients

Abstract: Perturbations in the gut microbiome have been associated with colorectal cancer (CRC), with the colonic overabundance of Fusobacterium nucleatum shown as the most consistent marker. Despite its significance in the promotion of CRC, genomic studies of Fusobacterium is limited. We enrolled 43 Vietnamese CRC patients and 25 participants with non-cancerous colorectal polyps to study the colonic microbiomes and genomic diversity of Fusobacterium in this population, using a combination of 16S rRNA gene profiling, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Another study reported similar results: Fusobacteria was higher in CRC than in tubular adenoma and sessile serrated adenoma/polyp [25]. Lastly, a recent study from Vietnam has shown that F. nucleatum were more abundant in tumor tissues compared to control in CRC patients [26 ]. Interestingly, Fusobacteria are conserved in CRC metastatic cancer cells.…”
Section: Fusobacteria In (Oral) Cancermentioning
confidence: 61%
“…Another study reported similar results: Fusobacteria was higher in CRC than in tubular adenoma and sessile serrated adenoma/polyp [25]. Lastly, a recent study from Vietnam has shown that F. nucleatum were more abundant in tumor tissues compared to control in CRC patients [26 ]. Interestingly, Fusobacteria are conserved in CRC metastatic cancer cells.…”
Section: Fusobacteria In (Oral) Cancermentioning
confidence: 61%
“…Previous work by Tran et al . has suggested that HGT may be responsible for fap2 and radD variation [66]. Here, we present analysis of TVa adhesin gene sequences that reveals highly mosaic gene structures shaped by recombination between different lineages of subspecies polymorphum and other F. nucleatum subspecies.…”
Section: Discussionmentioning
confidence: 91%
“…FadA adhesin was found to bind to E-cadherin and further modulate E-cadherin/β-catenin signaling to induce adenomatous polyposis coli mutation ( Rubinstein et al, 2013 ). Moreover, in both periodontal disease and CRC, FadA forms functional amyloid-like assemblies that serve as a scaffold to facilitate biofilm formation and confer acid tolerance ( Meng et al, 2021 ; Tran et al, 2022 ). Studies of F. nucleatum as a sole initiator have shown that it promotes oncogenesis via a variety of pathways, including upregulating CRC cell glycolysis and activating TLR4 signaling to manipulate the expression of miRNA21, which results in the proliferation of CRC cells in the murine model ( Yang et al, 2017 , p. 21; Hong et al, 2021 ).…”
Section: Colorectal Cancermentioning
confidence: 99%